Outdoor leadership theory and practice - Martin, Bruce 1969-; Breunig, Mary 1967-; Wagstaff, Mark 1959-; Goldenberg, Marni 1972- (Human Kinetics, 2017)
Through lessons, activities, and exercises, Outdoor Leadership, Second Edition, will help students master eight core competencies essential to outdoor and adventure leadership, develop professional portfolios, and prepare to be successful leaders.